Income Dependency on Non-timber Forest Products: An Empirical Evidence of the Indigenous People in Peninsular Malaysia - Saifullah, Md Khaled (Springer Verlag, 2018)
The indigenous people have been identified to be among the poorest and the most socioeconomically and culturally marginalized people all over the world. The main purpose of the paper is to explore the socioeconomic and demographic factors of indigenous people in Peninsular Malaysia in context of poverty and the role of income dependency of non-timber forest products (NTFP). The data were collected in 2014 and 2015 through primary and secondary sources. Partial least squares (PLS) method was used to analysis the data. PLS is a modeling technique that features multiple regression and principal component analysis. The study shows that still a large number of indigenous households is involved in the NTFP activities. But the communities are moving away from NTFP based income to cash-crop based income because of poor sustainable forest management and lack of forest property rights. However, NTFP have a significant role in the household income and contribute 24% of the average income. Moreover, the analysis shows that location is significant to the poverty. There should be a suitable sustainable forest management system which can teach these indigenous communities about proper way of NTFP gathering and given proper rights to forest land. Furthermore, education is not significant to indigenous people and there is a high rate of school dropout among them. The government should introduce a different education system for indigenous communities which will emphasize the importance of education to them.